13(t+4)=5(t-11)=35

Simple and best practice solution for 13(t+4)=5(t-11)=35 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13(t+4)=5(t-11)=35 equation:



13(t+4)=5(t-11)=35
We move all terms to the left:
13(t+4)-(5(t-11))=0
We multiply parentheses
13t-(5(t-11))+52=0
We calculate terms in parentheses: -(5(t-11)), so:
5(t-11)
We multiply parentheses
5t-55
Back to the equation:
-(5t-55)
We get rid of parentheses
13t-5t+55+52=0
We add all the numbers together, and all the variables
8t+107=0
We move all terms containing t to the left, all other terms to the right
8t=-107
t=-107/8
t=-13+3/8

See similar equations:

| 2x-(2-3x)=13 | | 25+40x=50+35x | | 3=3/4b-6 | | 4z/9+7=-4 | | 7x(9-x)+1/3(9-x)=0 | | 6a/5=41/2 | | 0.15x+0.18(50,000-x)=8,700 | | z/7+2=10 | | -(w+14)+2w-12=-18 | | 33-2x=19 | | 25-4/3x=-4/3x+35 | | 8n+8=180 | | 4(2+t)=3(3t-2)-16 | | 5x(x+2/3)+(x+2/3)=0 | | 2(x+2)/3=4(2x-6)/5 | | 7-3x=17+6x | | 0=10-3y | | 0.06(4t+4)=0.24(t-5)+1.44 | | 0.18(y-3)+0.16y=0.10y-1.5 | | 5(2x+1)-2=-1 | | -3w+7=-9w+29 | | 20=2(u-5)-5u | | -5v+3(v+5)=19 | | 3+11h=8h+3 | | 3²+12x-62=0 | | 4(x+2)=-3x+29 | | 5h=2-h=4h | | 3u+21=-9(u-1) | | Y=3x–9 | | 9(4–6x)=–20–(3–5x) | | -4x+6=3(x-5) | | 3(k-8)=10 |

Equations solver categories